A COMPARATIVE ANALYSIS OF THE CRIMINAL LAW FRAMEWORK FOR MENTALLY ILL MURDERERS: A CASE STUDY OF ASEAN COUNTRIES - Gunawan Widjaja (Adisam Publisher, 2025)
This research analyses the criminal legal framework applied to mentally ill homicide offenders in several ASEAN countries. The aim is to understand how each country deals with these cases, and evaluate the differences and similarities in legal approaches and implementation of psychiatric evaluations. This research reveals that there is significant variation in the way ASEAN countries draft and implement criminal laws relating to mentally ill offenders. While the general principle that mentally ill offenders require special treatment is recognised, the study results indicate major differences in rehabilitation policies, use of psychiatric evaluations, and sentencing practices. These findings point to the importance of integrating more holistic and rehabilitation-focused policies to support the recovery and reintegration of mentally ill offenders into society.